„Wyrąbywanie chodnika” do szkoły polskiej na Śląsku w okresie poplebiscytowym (PDF 1,69 MB) (Książnica Śląska, 2025)
In the post-plebiscite period in Silesia, the Polish education systembegan to arise and operate in challenging conditions. Poor housingconditions, lack of educated teaching staff and aggressive activitiesof German propaganda hindered work in this field. The author ofthe article recalls the figure of Professor Mieczysława Mitera-Dobrowolska, a teacher at the Women’s Junior High School in Katowice,at Plac Wolności, and an organizer of the Methodological Centerfor Teachers. The author devotes significant space and attentionto the merits of the first Polish teachers working with young peoplein Silesia, emphasizes the novelty and innovation of the methods andforms of education used at that time and describes the achievementsof Polish education.